IMAGINING THE FUTURE AND REWRITING THE PAST: THE 'NEW' HISTORY OF TURKISH CYPRIOTS - Inanc, Gul; Kizilyrek, Niyazi (Turkish Policy Quarterly, 2008)
As social, political and economic conditions of nations change, so national memory and national identity, will be redefined in ways that make them relevant to the new set of circumstances in which they find themselves. It is no coincidence (as in other societies) that the Turkish Cypriot community changed its history books in circumstances in which it imagined a different future for itself. Yet, how important this step will be in shaping the future for the next generation remains to be seen. Turkish Cypriots, who have been politically and economically isolated from the rest of the world for the last 30 years, recently took a very big step by returning to the classroom and by reconstructing and representing their past for a better future.